The impact of physical exercise, health effect, and harmony effect on young adults’ fertility attitudes: a study based on empirical analysis of 2023 CGSS data - Bu, Xiuxiu; Lu, Linbo; Li, Xinze; Cen, Cong (Frontiers in Public Health, 2025)
IntroductionFaced with a declining birth rate, China urgently needs to identify effective strategies to improve residents’ attitudes toward having additional children. This study investigates whether physical exercise, grounded in leisure theory and demographic principles, serves as a significant factor in promoting positive fertility attitudes.MethodsThis research employs a conceptual framework that identifies the prerequisites and inherent benefits of physical exercise. We then empirically test its influence using data from the 2023 Chinese General Social Survey (CGSS). The desire for another child is the key outcome variable, regressed on measures of sports participation. Robustness checks are conducted to address potential endogeneity, and a mediation analysis is performed to uncover the underlying pathways.ResultsThe results demonstrate that participation in sports activities substantially improves individuals’ fertility attitudes. This positive effect remains robust after controlling for endogeneity. The mediation analysis reveals that the relationship is driven by two significant pathways: first, through the enhancement of physical and mental health, and second, through the strengthening of family cohesion and overall life satisfaction.DiscussionThe findings confirm that physical exercise is a significant and positive predictor of fertility attitudes in China. The mechanisms operate through both bio-psychological and socio-familial channels. We conclude that public policies aimed at promoting accessible and appealing physical exercise can effectively complement existing fertility support measures, thereby providing a viable strategy to help optimize China’s national population policies.